Social support may buffer, to an extent, the impact of stigma on health-related quality of life among type 2 diabetes mellitus patients - Desmond Uchechukwu Onu; Christy Ngozi Obi-keguna; Osadebe Nnabuike Oguguam; Chukwuedozie K. Ajaero; Elisha John Igwe (Discover Public Health)
Abstract Type 2 diabetes patients often experience higher levels of stigma than the general population, which has been extensively documented to adversely impact their health-related quality of life (HRQoL). However, studies examining what factors could buffer this link, are lacking. We therefore explored social support as a moderator in the relationship between stigma and HRQoL among Type 2 diabetes mellitus (T2DM) Patients. Through a cross-sectional design, we conveniently sampled 150 T2DM patients from four health facilities in Nigeria, who were assessed using validated and reliable measures of diabetes-related stigma, quality of life, and social support. Results showed that the self-stigma domain of diabetes stigma was associated with poor HRQoL. Although social support significantly buffered the detrimental impacts of the "treated differently" and "blame and judgment" domains of stigma, it did not mitigate the adverse impacts of self-stigma on HRQoL. Therefore, in addition to enhancing social support among T2DM patients, interventions may also do well to incorporate therapeutic approaches aimed at addressing the unique challenges posed by self-stigma in this vulnerable population.